+0  
 
0
641
2
avatar

use first principal to find the derivative of 

f(x)=sin^2(2x)

\(f(x)=sin^2(2x)\)

Guest Feb 13, 2016

Best Answer 

 #2
avatar+87333 
+5

Note that :

 

 sin^2(2x)   = [1 - cos(4x)]/ 2     ......so we have.....

 

[ 1 - cos4(x + h)] / 2] * [ 1/h]    -    [1 - cos(4x)] / 2 * [ 1/h ] =

 

[1 - cos(4x + cos4h)] / 2h   - [1 - cos(4x)] 2h  =

 

[cos(4x)  -  cos(4x + 4h) ] / 2h   =

 

[ cos(4x)  - [cos4xcos4h  - sin4xsin4h] ] / 2h  =

 

[ cos4x ][1 - cos4h] / 2h    +  sin4xsin4h/ 2h        [multiply top/bottom of both fractions by 2]

 

[2cos4x] [(1 - cos4h) / 4h ] +   [2sin4x] [sin4h/ 4h ]       let h →  0

 

[2cosx * 0]  +  [2sin4x * 1 ]  =

 

2sin4x  =

 

2sin(2x + 2x)  =

 

2[ sin2xcos2x + sin2xcos2x]  =

 

2 [ 2 * sin2xcos2x]  =

 

4[sin2x] [cos2x]

 

-------------------------------------------------------------------------

 

Note that :   [sin(2x)]^2  =  [sin2x ] * [sin2x]     (1)

 

And using the Product Rule, the derivative  of (1)  =

 

[2cos2x] [sin2x] + [sin2x][ 2 cos2x]  =

 

[2cos2x] [ sin2x + sin2x]  =

 

[2cos2x] [2sin2x] =

 

4[sin2x][cos2x]

 

 

cool cool cool

CPhill  Feb 13, 2016
edited by CPhill  Feb 13, 2016
edited by CPhill  Feb 13, 2016
edited by CPhill  Feb 13, 2016
 #1
avatar
+5

Find the derivative of the following via implicit differentiation:

d/dx(f(x)) = d/dx(sin^2(2 x))

The derivative of f(x) is f'(x):

f'(x) = d/dx(sin^2(2 x))

Using the chain rule, d/dx(sin^2(2 x)) = ( du^2)/( du) ( du)/( dx), where u = sin(2 x) and ( d)/( du)(u^2) = 2 u:

f'(x) = 2 d/dx(sin(2 x)) sin(2 x)

Using the chain rule, d/dx(sin(2 x)) = ( dsin(u))/( du) ( du)/( dx), where u = 2 x and ( d)/( du)(sin(u)) = cos(u):

f'(x) = cos(2 x) d/dx(2 x) 2 sin(2 x)

Factor out constants:

f'(x) = 2 d/dx(x) 2 cos(2 x) sin(2 x)

Simplify the expression:

f'(x) = 4 cos(2 x) (d/dx(x)) sin(2 x)

The derivative of x is 1:

f'(x) = 1 4 cos(2 x) sin(2 x)

Simplify the expression:

f'(x) = 4 cos(2 x) sin(2 x)

Expand the left hand side:

Answer: |f'(x) = 4 cos(2x) sin(2x) =f'(x) = 2 sin(4x)

Guest Feb 13, 2016
 #2
avatar+87333 
+5
Best Answer

Note that :

 

 sin^2(2x)   = [1 - cos(4x)]/ 2     ......so we have.....

 

[ 1 - cos4(x + h)] / 2] * [ 1/h]    -    [1 - cos(4x)] / 2 * [ 1/h ] =

 

[1 - cos(4x + cos4h)] / 2h   - [1 - cos(4x)] 2h  =

 

[cos(4x)  -  cos(4x + 4h) ] / 2h   =

 

[ cos(4x)  - [cos4xcos4h  - sin4xsin4h] ] / 2h  =

 

[ cos4x ][1 - cos4h] / 2h    +  sin4xsin4h/ 2h        [multiply top/bottom of both fractions by 2]

 

[2cos4x] [(1 - cos4h) / 4h ] +   [2sin4x] [sin4h/ 4h ]       let h →  0

 

[2cosx * 0]  +  [2sin4x * 1 ]  =

 

2sin4x  =

 

2sin(2x + 2x)  =

 

2[ sin2xcos2x + sin2xcos2x]  =

 

2 [ 2 * sin2xcos2x]  =

 

4[sin2x] [cos2x]

 

-------------------------------------------------------------------------

 

Note that :   [sin(2x)]^2  =  [sin2x ] * [sin2x]     (1)

 

And using the Product Rule, the derivative  of (1)  =

 

[2cos2x] [sin2x] + [sin2x][ 2 cos2x]  =

 

[2cos2x] [ sin2x + sin2x]  =

 

[2cos2x] [2sin2x] =

 

4[sin2x][cos2x]

 

 

cool cool cool

CPhill  Feb 13, 2016
edited by CPhill  Feb 13, 2016
edited by CPhill  Feb 13, 2016
edited by CPhill  Feb 13, 2016

7 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.